Physical Activity, Sedentary Behavior, and the Metabolic Syndrome in Minority Youth - HSU, YA-WEN (Med Sci Sports Exerc, 2011)
PURPOSE: This study aimed to determine the associations among physical activity, sedentary behavior, and the metabolic syndrome (MetS) in Latino and African American youth using both subjective and objective measures of activity levels. METHODS: Cross-sectional data from 105 participants from three pediatric obesity studies that share a core set of methods and measures (Latino 74%, female 75%, mean age =13 ± 3 yr) were used. Measures included moderate-to-vigorous physical activity and sedentary behavior by accelerometry and 3-Day Physical Activity Recall (3DPAR), fat and lean tissue mass by BodPod™, fasting glucose, lipids, blood pressure, and waist circumference. Associations between physical activity, sedentary behavior, and MetS were examined using ANCOVA, Pearson correlations, partial correlations, and logistic regressions with adjustments for age, sex, ethnicity, fat and lean mass, and pubertal Tanner stage. RESULTS: Accelerometry data showed that greater time engaging in moderate-to-vigorous physical activity was related to lower odds of the MetS (odds ratio = 0.49, 95% confidence interval = 0.25–0.98), independent of sedentary behavior and covariates, and inversely correlated with fasting glucose (r = −0.21, P = 0.03) and systolic blood pressure (r = −0.25, P = 0.01), adjusting for covariates. Data from the 3DPAR showed that higher levels of sedentary behavior were related to higher odds of the MetS (odds ratio = 4.44, 95% confidence interval = 1.33–14.79), independent of moderate-to-vigorous physical activity and covariates, negatively correlated with HDL-cholesterol (r = −0.21, P = 0.04) and positively correlated systolic blood pressure (r = 0.26, P = 0.009), adjusting for covariates. CONCLUSIONS: Future interventions aiming to improve metabolic health in youth should target both the promotion of physical activity and the reduction of sedentary behavior. Subjective and objective measures should be used in conjunction to better capture activity behaviors.